Sensory Values of Chicken Sausage with the Addition of Rendang Spices - Anita Khairiyah Nasution; Afriani Sandra; Deni Novia; Rusmana Wijaya Setia Ningrat (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2024)
This study aimed to determine the best percentage of additional Rendang spices in the sensory analysis of chicken sausages. This study was conducted using an experimental research method with a completely randomized design (CRD); it has five treatments, i.e., P1 = 0%, P2 = 5%, P3 = 10%, P4 = 15%, and P5 = 20%. Sensory preference and sensory intensity tests (taste, flavor, color, and texture) of treated samples were determined. The results of this study indicated that the addition of Rendang spices to chicken sausages has a significantly different effect (P<0.05) on preference tests (taste, flavor, color, and texture) and intensity tests (taste, flavor, color, and texture). However, the results showed no significant (P>0.05) effect on the preference tests (texture). It was concluded that adding Rendang spices to chicken sausages had sensory ratings acceptable to the panelists.